Discussion of LTE Backhaul Service-Oriented PTN L3 Core Network Design - Jian Wang; Can Liang (Dianxin kexue)
The TD-LTE network scenario PTN core layer L3 networking architectures and networking ideas were described. Firstly, the TD-LTE radio network requirements were introduced and the existing metro transport network appropriate framework was described. Secondly, the current PTN L3 functions, PTN+CE bearer network architecture, PTN L3 network detailed deployment and designing were analyzed. Finally, PTN metro L3 network evolution was analyzed, a reference to the future development of the network was provided.